Monitoring land use and land cover changes due to extensive gold mining, urban expansion, and agriculture in the Pra River Basin of Ghana, 1986–2025. (3rd August 2018) - Awotwi, Alfred; Anornu, Geophrey Kwame; Quaye‐Ballard, Jonathan Arthur; Annor, Thompson
Abstract: This study used the double cumulative curve and visual image interpretation methods for the selection of spatiotemporal Landsat data to evaluate the land degradation by anthropogenic activities in the Pra River Basin (PRB) of Ghana. Unsupervised and supervised classification procedures were used to map the land use and land cover (LULC) distribution from 1986 to 2016. Assessment of LULC showed that the PRB has been subjected to six different rates of land degradation in the years 1986, 2000, 2004, 2008, 2013, and 2016. This is due to increase in settlement, cropland, and mining activities to about 130%, 198%, and 304%, respectively. The Markov chain and cellular automation integrated model was successful in predicting LULC distribution in 2016 and the outcomes were comparable to the actual LULC for 2016. The projected LULC for 2025 showed that land degradation is significant in the western and the eastern parts where cropland and forest are, respectively, converted to mining activity. The northern, southern, and middle parts of PRB are expected to experience high settlement expansion, sedimentation in the rivers, and cropland expansion, respectively. The results will aid natural resources management, planning, and sustainable development at PRB. In addition, the research method serves as guideline for other related studies in an attempt to investigate, quantify, and project LULC change in forest ecological areas.